Theoretical Investigations on the Molecular Structure, Vibrational Spectroscopic Analysis of 2,4-dinitro-1-naphthol - and P.S. Joseph2, N. Raghothaman1* (Recent Research in Science and Technology, 2010)
Abstract The FT-IR & FT-Raman spectra of 2,4-dinitro-1-naphthol have been recorded in the region 4000- 400 cm-1 and 3500-50 cm-1 respectively. The spectra were interpreted with the aid of normal coordination analysis following full structure optimization and force field calculations on the Density Functional Theory (DFT) use in the standard B3LYP method and 6-31+G basis set combination. A close agreement was achieved between the observed and calculated frequencies by refinement of the scale factors. Keywords: FTIR, FT-Raman Spectra, DFT calculations, Vibrational analysis, 2,4-dinitro-1-naphthol